MADRASAH EDUCATION IN THE DIGITAL ERA THROUGH MANAGEMENT STRATEGIES FOR ACADEMIC AND CHARACTER SUCCESS - Hastutik, Sepna Yuni (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to explore the application of TQM as  the primary strategy for improving the quality of educational institutions. By understanding the nature of TQM and its impact on educational institutions, it is hoped that we can make a significant contribution in facing various challenges and competition in the education sector. In this way, we can form educational institutions that are not only of high quality but also capable of producing graduates who are ready to compete on the global stage. This research uses a qualitative case study type method by conducting research aimed at describing problems and analyzing the problems that occur. Researchers collected data through several stages, such as observation and direct observation at the research site. Interview interviewing several informants at the research location. Observation, visiting research locations. Documentation study, analyzing documents related to research. The research was conducted at the MI Tarbiyatul Islam institution in Kandangjati Kulon, Kraksaan, and Probolinggo. Based on the research results, several innovations adopted by MI Tarbiyatul Islam include (1) Integrated Learning Technology. This institution combines modern technology in its learning process, including educational software, interactive learning applications, and online platforms. This increases student engagement and facilitates real-time measurement and analysis of learning data. (2) Training and Development of Human Resources (HR): Realizing that the excellence of an institution is very dependent on the quality of human resources, MI Tarbiyatul Islam routinely provides training and development to teachers and administrative staff.